Membina Karakter Anak Sekolah Dasar Melalui Pembelajaran Hak Asasi Manusia dengan Pendekatan Case Study: Developing Character of Children Elementary School through Human Rights Learning with a Case Study Approach - Mellisa Towadi; Lisnawaty W. Badu; Waode Mustika (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2022)
The current method that is very appropriate for limiting children's social interactions while preventing the practice of minor human rights violations is to get more intense in inviting children to actualize what they see and read into human rights theory through a case study approach. The research method used in this theory is the Creswell case study, the focus of the case study is the specification of the case in an event, whether it includes individuals, cultural groups or a portrait of life. The results of this study indicate that elementary school children more easily understand the theory that is transformed in the form of the case method by the teacher. This is because the case study approach is carried out based on practice or actualization through a good habit process.